-2p+8=5-(9p+6)

Simple and best practice solution for -2p+8=5-(9p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2p+8=5-(9p+6) equation:


Simplifying
-2p + 8 = 5 + -1(9p + 6)

Reorder the terms:
8 + -2p = 5 + -1(9p + 6)

Reorder the terms:
8 + -2p = 5 + -1(6 + 9p)
8 + -2p = 5 + (6 * -1 + 9p * -1)
8 + -2p = 5 + (-6 + -9p)

Combine like terms: 5 + -6 = -1
8 + -2p = -1 + -9p

Solving
8 + -2p = -1 + -9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '9p' to each side of the equation.
8 + -2p + 9p = -1 + -9p + 9p

Combine like terms: -2p + 9p = 7p
8 + 7p = -1 + -9p + 9p

Combine like terms: -9p + 9p = 0
8 + 7p = -1 + 0
8 + 7p = -1

Add '-8' to each side of the equation.
8 + -8 + 7p = -1 + -8

Combine like terms: 8 + -8 = 0
0 + 7p = -1 + -8
7p = -1 + -8

Combine like terms: -1 + -8 = -9
7p = -9

Divide each side by '7'.
p = -1.285714286

Simplifying
p = -1.285714286

See similar equations:

| -12x=288 | | m(7+m)=78 | | -47+4x=34+7x | | 12x^2y-16x^2-18y+24=0 | | 150=-7x+5(-x+6) | | 10x^2+28x-96=0 | | 8c-5c-6c= | | 6*0-5y=-30 | | -x(x-8)+2(x+2)=x+9 | | -4x^2+3x-5=0 | | 0.18(18)+0.03x=0.09(12+x) | | 6x-5*0=-30 | | -(3y+3)-(-2-5)=-5 | | 2x-6=2x-8 | | -7(3b+2)+(22b-6)=0 | | x/1.2=1.7 | | 2.6q-3.6-3.4=1.8q-5.4 | | 2x-(3x-8)= | | 4x-3=-27 | | 14=3x+4x | | 10x-6x+4=21x | | 5x*4y=3x*2y | | 5*4y=3*2y | | -x^2+8x+16=0 | | v(v+5)= | | 4X^2+20x+100=109 | | 2+4y=25 | | 6*1h=51 | | 3+17b=-422 | | 8w=8w+42 | | 7=z+2 | | 4(2y+1)=4(3y-10) |

Equations solver categories